Penerapan Prinsip-Prinsip Good Corporate Governance Pada Perbankan Syariah - Safnah Soleha; Adelia Safitri; Maulida Rahma; Ahmad Wahyudi Zein (Jurnal Ekonomi dan Bisnis Digital, 2025)
The implementation of Good Corporate Governance (GCG) in Islamic banking is a crucial factor in enhancing public trust and ensuring that bank operations are in accordance with Islamic principles. This study aims to analyze the implementation of GCG principles, including transparency, accountability, responsibility, professionalism, and fairness, as well as the challenges faced, particularly in the digital era. The study employed a literature review method, reviewing various sources related to the concept of GCG, Islamic banking, and the role of the Sharia Supervisory Board (SSB). The study results indicate that the implementation of GCG in Islamic banks has been quite successful, particularly in terms of information transparency and the division of supervisory functions. However, weaknesses remain in the effectiveness of the SSB, the quality of risk disclosure, and the competence of human resources. Digitalization also creates new opportunities and risks that require strengthening information technology-based governance. Overall, improving the quality of GCG is necessary for Islamic banks to maintain stability, improve performance, and strengthen public trust.